ANALISIS PENGARUH PERTUMBUHAN EKONOMI, ANGKATAN KERJA, DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP TINGKAT PENGANGGURAN TERBUKA DI PROVINSI MALUKU - Addie Sabta Ibiyantoro; Niniek Imaningsih (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study describes economic development aimed at the advancement of society. Achieving this progress requires community employment opportunities which ultimately lead to income distribution among the population, and making many changes to support the country's development and high economic miracle. On the other hand, of course, there is a gap between job opportunities and an unbalanced workforce, so that with the lack of job opportunities and the increasing number of job seekers, it will have a negative impact on the creation of unemployment. This study aims to determine the effect of Economic Growth (X1), Labor Force (X2), and Human Development Index (X3) on the Open Unemployment Rate (Y) in Maluku Province from 2007-2021. The analysis applied to this study is multiple linear regression and testing with the BLUE assumption is carried out in the study to prove the results that this study passed the classical assumption test. The results of this study indicate that Economic Growth has no effect on the Open Unemployment Rate, the Human Development Index has no effect on the Open Unemployment Rate, and the Poverty Level has a positive (not significant) on the Open Unemployment Rate in Maluku Province